Use Of Instagram As A Media For Information On Pptq Activities Khoirul Ummah Hidayatullah Pantoloan Using Instagram as an Information Media PPTQ Khoirul Ummah Hidayatullah Pantoloan - Muhammad Ibadullah Sholihun (LPPM Universitas Tadulako, 2021)
Using Instagram as Information Media for PPTQ Activities Khoirul Ummah Hidayatullah Pantoloan. Communication Science Study Program, Faculty of Social and Political Sciences, Broadcasting Concentration, Tadulako University Under the Guidance of Stepanus Bo'do and Kudratullah. This research aims to find out how the administrators of the Tahfidzul Qur'an Khoirul Ummah Islamic Boarding School (PPTQ KHUMMAH) Hidayatullah Pantoloan use social media Instagram to disseminate information about the activities of PPTQ Khoirul Ummah students. This research uses a descriptive type of research with a qualitative approach, with data collection procedures using: observation, interviews, and documentation. The theory used is Uses and Gratification. The research results show that the use of Instagram media by Islamic boarding school administrators is very helpful in disseminating information about the activities of the PPTQ Khoirul Ummah Hidayatullah Pantoloan students, by utilizing the features on Instagram as a means of disseminating information about the students' activities. The photo title or caption is a feature that really helps administrators and makes it easier for the public to find out what activities are being carried out by PPTQ Khoirul Ummah students. Meanwhile, the Geotag feature is a feature that can make it easier for audiences/people who want to visit Islamic boarding schools by placing location markers on each post. The mentioned feature really helps administrators increase the number of visitors to Khoirul Ummah's PPTQ Instagram account by adding the aroba sign (@) in posts. The comments column feature is also very helpful for the PPTQ Khoirul Ummah administrators to find out how Instagram users respond when they see posts on the PPTQ Khoirul Ummah account. The following feature on Instagram makes it easier for administrators to follow other users' Instagram accounts so that the audience we follow will see Khoirul Ummahdi's photo, video, and PPTQ flyer posts on their home page. Instastory This feature is very helpful in sharing the latest information. Stories are more